ARRANJO PRODUTIVO LOCAL DAS GÊMEAS DO IGUAÇU: UMA ALTERNATIVA PARA O DESENVOLVIMENTO TERRITORIAL? PONTA GROSSA 2007 - Haliski, Antonio Marcio (2007)
Is the investment in Local Productive Arrangements (APLs) an alternative to the territorial development? This is the issue proposed to be answered. It is used to defend that to argue the relevancy of the territorial approach to explain the process of economic development is a significant contribution to society. It is analyzed in this the thesis the case of the APL of the wood at União da Vitória-PR and Porto União-SC cities, known as “the Iguaçu’s twin”. The central approach is in the cooperation between the involved ones. It is believed that credit that diagnostic badly formulated the social context in which the boarded APL is inserted, makes the formularization difficult and try to remake them. This study emphasizes the lack of existing cooperation between the actors who act in the territory, wondering to analyze what this can mean for the advance of this idea about the decentralized territorial development.